Inhibition of Staphylococcus aureus by cinnamaldehyde and its effect on sensory properties of milk. (September 2019) - Babic, M; Glisic, M; Zdravkovc, N; Djordjevic, J; Velebit, B; Ledina, T; Baltic, M Z; Boskovic, M
Abstract: The antibacterial activity of cinnamaldehyde was evaluated against S. aureus experimentally inoculated (10 3 CFU/mL) in UHT-pasteurized milk, which was treated with different concentrations of the cinnamaldehyde (0.1% and 0.05%) and stored at 4 °C for 12 days. The MIC of cinnamaldehyde was 160 μg/ml. During the storage period, S. aureus counts in milk were reduced by 0.35-2.77 log CFU/mL. Significantly greater decreases were observed when cinnamaldehyde was added, regardless of the concentration used, compared with the control. A triangle test showed that panellists could detect the difference between milks with different concentrations of cinnamaldehyde (P<0.01). These results suggest that by adding 0.05% cinnamaldehyde to milk, the safety of the milk can be increased and a pleasant, desirable flavour can be obtained.